Pelestarian Mada Oi Tula Sebagai Sumber Mata Air Bagi Masyarakat Desa Punti - Bagus Shaburu; Nurmelisa Nurmelisa; Junaidin Junaidin; Adyatma Fadilah; Maulana Muslimin; Defis Purnama Sari; Ismunandar Ismunandar; Muhammad Badar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Mada Oi Tula, as the main water source for the residents of Punti Village, plays a crucial role in supporting daily needs and local agricultural activities. This study aims to explore the practices of preserving this water source and the challenges faced by the community. Employing a qualitative method with a case study approach, data were gathered through in-depth interviews with traditional leaders, community members, and village authorities, as well as through Focus Group Discussions (FGDs). The findings reveal that the preservation of Mada Oi Tula is significantly influenced by local cultural values and the community's spirit of mutual cooperation. However, challenges such as deforestation and land use changes pose major threats, emphasizing the need for collaborative efforts between the community and relevant stakeholders to ensure the sustainability of this water source.